The influence of human use on rangeland biodiversity in Ghibe Valley, Ethiopia, as affected by natural resource use changes and livestock disease control - Reid, Robin S.; Wilson, C.J.; Kruska, Russell L. (Society for Range Management, 1996)
In southwestern Ethiopia, recent chaotic events, changes in land tenure and introduction of tsetse fly [Glossina tachinoides] control have precipitated changes in the use of land and other natural resources. In turn, these changes have initiated shifts in rangeland biodiversity. Unexpectedly, small-holder cultivated fields contained more tree and bird species than less-used rangelands. Conversion of rangelands to agriculture sustained biodiversity unless the rangelands were converted into large, mechanized farms (involving tree removal) or if conversion occurred in species-rich riparian corridors.